The Role of the State in Protecting Intellectual Property Rights through Policies and Legal Mechanisms in Indonesia - Dani Firlandani; Sherry Cristina; Ranto Rey Sambo; Agus Septima Ridwan (Sean Institute, 2026)
Intellectual Property Rights constitute a strategic legal instrument for fostering creativity, innovation, and sustainable economic development. The state plays a pivotal role in ensuring effective protection of Intellectual Property Rights through coherent policies and enforceable legal mechanisms. This study aims to examine the role of the state in protecting Intellectual Property Rights in Indonesia by analyzing existing legal frameworks and policy approaches. The research employs a normative juridical method with statutory and conceptual approaches, relying on an examination of national regulations and relevant legal literature. The findings indicate that the state functions as a regulator, facilitator, and law enforcer in the protection of Intellectual Property Rights through regulatory formulation, administrative registration systems, and civil, criminal, and administrative enforcement mechanisms. Nevertheless, the effectiveness of such protection remains constrained by limited public legal awareness and challenges in law enforcement implementation. Strengthening legal policies, enhancing public literacy on Intellectual Property Rights, and improving institutional coordination are therefore essential to achieve comprehensive, effective, and equitable protection.